As salas de recurso multifuncionais como instrumento de apoio à educação especial em perspectiva inclusiva: um olhar decolonial - Rosa, Jéssica Danieli Ramos da (2024)
This master's research is linked to the Educational Policy Research line of the Postgraduate Program in Education at the University of Passo Fundo (UPF/RS). This is a qualitative investigation, based on dialectical methodology, guided by bibliographic and documentary research procedures. The problem is formulated as follows: do multifunctional resource rooms, profiled by legal force after the 2008 Policy (Brasil, 2008), have characteristics that allow school inclusion to be enhanced? To support the work, studies by researchers in the area of ​​special education are presented, such as Baptista (2011, 2013) and Kassar (2011), Walsh's decolonial pedagogy, Meneses' Epistemologies of the South; Santos (2010), as well as the studies by Maldonado-Torres. The objective is to analyze the way in which special education has developed to date; identify which space is the Multifunctional Resource Room (SRM); questioning when the SRM becomes the only space in which people with disabilities can express themselves according to their peculiarities; analyze whether the school has SRM space; compare what is foreseen in the legislation and what is experienced when working in the Resource Room (SR); know which professional is the one who carries out the work in SR; understand how decoloniality enters special education; identify what an SRM would look like with instruments that enhance inclusive education. The dissertation is structured into three chapters. The first consists of presenting the research, reviewing special education based on the 1961 Education Guidelines and Bases Law and the developments in the schooling of people with disabilities from that period onwards to arrive at existing legislation and policies in contemporary times. . The second is characterized by the construction of the theoretical contribution based on the analysis of documents guiding the institutionalization of Resource Rooms and the bibliographic review with relevant authors in this area. In the third, an analysis is developed about the special education that we “want” and that which is presented to us, making notes on what an SRM with an inclusive and decolonial character would be like. It is concluded that repeating subalternization strategies means using a practice that moves towards concepts crystallized in the discourse about people with disabilities. For this reason, breaking with these actions is not easy, but needs to be carried out in school routines and in the implementation of public policies that meet school needs.